Thyroid function in obese Korean children and adolescents: Korea National Health and Nutrition Examination Survey 2013-2015 - Young Min An; Soon Jeong Moon; Soon Ki Kim; Young Ju Suh; Ji Eun Lee (Korean Society of Pediatric Endocrinology, 2018)
Purpose In recent years, there has been an increasing focus on thyroid function in pediatric obese patients, but no nationwide study evaluating the relationship between thyroid function and obesity has yet been conducted in Korea. We aimed to evaluate thyroid dysfunction in obese Korean children. Methods We analyzed the associations between obesity and thyroid hormone levels among 975 Korean boys and girls aged 10-18 years and who participated in the Korean National Health and Nutrition Examination Survey VI (2013-2015). Results Average serum thyrotropin (TSH) and serum free thyroxine (fT4) levels in the nonobese group were 2.7±0.1 μIU/mL and 1.3±0.0 ng/dL, respectively, and those in the overweight group were 3.1±0.2 μIU/mL and 1.2±0.0 ng/dL. Serum TSH level was significantly higher in the abdominal obesity group than in the normal group (P=0.023). fT4 level was significantly lower in both the overweight and abdominal obesity groups than in the normal group (P<0.001, P=0.014). Serum TSH level was associated positively with abdominal obesity and levels of high-density lipoprotein cholesterol and triglyceride. Serum fT4 level was negatively correlated with abdominal obesity (P=0.014). Conclusions Korean children with abdominal obesity showed increased TSH and decreased fT4 levels compared to normal children.